Case Study Research: Putting the Quant Into the Qual. (August 2016) - Elman, Colin; Gerring, John; Mahoney, James
Case studies are usually considered a qualitative method. However, some aspects of case study research—notably, the selection of cases—may be viewed through a quantitative template. In this symposium, we invite authors to contemplate the ways in which case study research might be conceived, and improved, by applying lessons from large- n cross-case research.